"Before" the hall of kingdoms - R. de la Flor, Fernando (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The Hall of the Kingdoms, a substantial part of a lost Buen Retiro Palace, after centuries of suffering all kinds of vicissitudes, is going to be "restored." In this delicate moment, a resemantization such as this one is actually generated from a research by two WASPs carried out in 1981 (Un palacio para el rey "A Palace For The King"), and from the definitive intervention of an architect, the also WASP Norman Foster. Thus, this place, which became for more than three centuries the motor of a self-policy and an identity way, a true "[symbolic] centrer of the world", is left in the hands of "Hispanizers."